A Traditional Chinese Medicine, Maoto, Suppresses Hepatitis B Virus Production - Rahman, Md. Arifur; Ueda, Keiji; Honda, Tomoyuki (Frontiers in Cellular and Infection Microbiology, 2021)
Worldwide, millions of people suffer from hepatitis B virus (HBV) infection, putting them at a high risk of death from liver cirrhosis and cancer. Although effective anti-HBV drugs have been developed, current drugs have some limitations, as most of them have a risk of significant side effects. Therefore, the discovery of safe and effective anti-HBV drugs is still needed. Natural compounds are considered sources of novel, safe and effective therapeutics. In this study, we screened a library of Kampos, traditional herbal medicines, for suppression of HBV production. Among them, we found that maoto reduced extracellular HBV DNA but not extracellular HBsAg during HBV infection, suggesting that it suppressed HBV production by interfering with HBV nucleocapsid incorporation into viral particles. Furthermore, we revealed that maoto reduced the expression of a host gene, Tropomyosin β chain (TPM2), whose downregulation also suppressed HBV production, similarly to maoto. Since the safety of maoto has been already confirmed, maoto can be considered a candidate anti-HBV agent if the effect is confirmed in vivo. In addition, our findings also suggest TPM2 as a novel molecular target for the development of anti-HBV agents.